Nitrogen modified metal composite material and preparation method and application thereof
By carbonizing native biomass and its derivatives in ethylene glycol containing nitrogen precursors and forming alloy catalytic sites, the problems of low catalyst activity and harsh reaction conditions in the existing technology are solved, and efficient catalytic monosaccharide oxidation is achieved. For the effect of sugar and acid.
Patent Information
- Application Number
- CN202411442799.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
AI Technical Summary
The existing chemical synthesis of sugar acid methods has problems such as low catalyst activity, poor circulation performance, high reaction temperature and difficulty in separating alkaline substances.
By carbonizing native biomass and its derivatives in ethylene glycol containing nitrogen precursors, the bimetal is reduced and loaded on the nitrogen-modified functional carbon carrier to form an alloy catalytic site for catalyzing the oxidation of monosaccharides into sugars. acid.
Efficient monosaccharide oxidation reaction was achieved, with a glucose conversion rate of 100%, gluconic acid yield of 81.7%, and gluconic acid yield of 13.1%, providing a theory for the chemical catalytic oxidation of agricultural waste such as straw to directly synthesize sugar acids. Base.
Smart Images

Figure CN119327498A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical synthesis, and in particular relates to a nitrogen-modified metal composite material and a preparation method and application thereof. Background Art
[0002] Chemical catalytic oxidation is considered a sustainable method for synthesizing sugar acids. Lignocellulosic biomass is mainly composed of three components: cellulose (30-50%), hemicellulose (15-35%) and lignin (10-20%). It has the advantages of being cheap, clean, renewable, and not competing with food. Therefore, it can be used as an ideal carbon source for preparing functional biochar and as a raw material for producing sugar acids.
[0003] Sugar acids have attracted much attention due to their wide range of uses. They can be used as additives in the food and pharmaceutical industries, as components of amphiphilic polymers, or as green chelating agents in metal extraction. They have potential for application in many fields such as food, medicine, and chemical industry. Despite this, existing methods for chemically synthesizing sugar acids still have some challenges. For example, the catalyst activity is low, the cycle performance is poor, and the temperature required for the reaction is high. In addition, most catalytic systems require the additional addition of alkaline substances, which are difficult to separate. In response to these problems, the present invention proposes a nitrogen-modified metal composite material, a preparation method, and an application thereof. Summary of the invention
[0004] The purpose of the present invention is to provide a nitrogen-modified metal composite material and a preparation method and application thereof, aiming to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing a nitrogen-modified metal composite material comprises the following steps:
[0007] Step 1, dissolving a platinum salt and a transition metal salt in ethylene glycol to obtain a mixture; the platinum salt comprises chloroplatinic acid and / or platinum diacetylacetonate, and the transition metal salt comprises zinc chloride and / or nickel nitrate and / or cupric chloride;
[0008] Step 2: adding the native biomass and its derivatives and the nitrogen precursor to the mixture obtained in step 1, stirring and solvent thermal treatment, centrifuging, washing and drying the product after solvent thermal treatment in sequence to obtain a nitrogen-modified metal composite material; the native biomass and its derivatives include rice straw and / or lignin and / or glucose, and the nitrogen precursor includes glutamic acid and / or glycine and / or urea and / or ammonium sulfate.
[0009] Furthermore, in step 1, the molar ratio of the platinum salt to the transition metal salt is (0.5-1):(1-10).
[0010] Furthermore, the amount of ethylene glycol added in step 1 is 10 to 30 mL.
[0011] Furthermore, in step 2, the mass ratio of the native biomass and its derivatives to the platinum salt is (2-5):1.
[0012] Furthermore, in step 2, the molar ratio of the nitrogen precursor to the platinum salt is (1-5):1.
[0013] Furthermore, in step 2, the stirring speed is 300-1000 rpm, and the stirring time is 0.5-2 h; the temperature of the solvent thermal treatment is 150-250° C., and the solvent thermal treatment time is 6-18 h.
[0014] A nitrogen-modified metal composite material prepared according to the preparation method described above, wherein the metal is bimetallic alloy nanoparticles, and the nitrogen-modified functional carbon carrier obtained by carbonizing native biomass and its derivatives in ethylene glycol containing a nitrogen precursor is a nitrogen-modified biochar carrier.
[0015] An application of the nitrogen-modified metal composite material described above in catalyzing the preparation of sugar acid from monosaccharides, specifically comprising: using the nitrogen-modified metal composite material as a catalyst, mixing it with monosaccharides, ultrapure water, and oxygen, and then performing an oxidation reaction to obtain sugar acid; after the reaction is completed, cooling with running water and releasing the pressure in the reactor, taking the supernatant and performing qualitative and quantitative analysis of the product by high performance liquid chromatography (HPLC);
[0016] The monosaccharides include xylose and glucose. Xylose is converted into xylonic acid through oxidation reaction, and glucose is converted into gluconic acid and glucaric acid through oxidation reaction.
[0017] Furthermore, the temperature of the oxidation reaction is 60-110°C or 25-50°C; when the reaction temperature is 60-110°C, the reaction time is 10-120 minutes; when the reaction temperature is 25-50°C, the reaction time is 1-5 days.
[0018] Furthermore, the mass concentration of monosaccharide in the mixed solution of the nitrogen-modified metal composite material, monosaccharide, ultrapure water and oxygen is 1-10%; the mass ratio of the nitrogen-modified metal composite material to monosaccharide is 1:(2-10); and the oxygen pressure is 0.1-1.4 MPa.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention carbonizes the original biomass and its derivatives in ethylene glycol containing nitrogen precursors, and at the same time, the bimetal is reduced and loaded on the nitrogen-modified functional carbon carrier to form an alloy catalytic site. The alloy catalytic site is conducive to the adsorption of monosaccharides, promotes mass transfer, and promotes the oxidation of monosaccharides to the final product sugar acid, thereby realizing the efficient monosaccharide oxidation reaction, and providing a theoretical basis for the direct synthesis of sugar acid by chemical catalytic oxidation of agricultural waste such as straw. Monosaccharides include xylose, glucose, etc.; the product sugar acid includes xylonic acid, gluconic acid, glucaric acid, etc. The results show that the glucose conversion rate is 100%, the gluconic acid yield is 81.7%, and the glucaric acid yield is 13.1%. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a transmission electron microscope image of the nitrogen-modified metal composite material prepared in Example 1.
[0022] Figure 2 This is the XPS spectrum of the Pt 4f orbital of the nitrogen-modified metal composite material prepared in Example 1.
[0023] Figure 3 This is the infrared spectrum of the nitrogen-modified metal composite material prepared in Example 1.
[0024] Figure 4 This is a curve diagram showing the change in the yield of gluconic acid produced by catalytic conversion of glucose into gluconic acid by the nitrogen-modified metal composite material prepared in Example 3 under different reaction temperature conditions as a function of reaction time. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0026] One embodiment of the present invention provides a method for preparing a nitrogen-modified metal composite material, comprising the following steps:
[0027] (1) dissolving a platinum salt and a transition metal salt in ethylene glycol to obtain a mixture;
[0028] Wherein, the platinum salt includes chloroplatinic acid and / or diacetylacetonate platinum, preferably chloroplatinic acid. The transition metal salt includes zinc chloride and / or nickel nitrate and / or cupric chloride, preferably zinc chloride. The present invention has no particular limitation on the sources of the metal salt and ethylene glycol, and commercial products known to those skilled in the art can be used.
[0029] The molar ratio of the platinum salt to the transition metal salt is preferably (0.5-1): (1-10), more preferably 1: 6. The molar ratio of the platinum salt to the transition metal salt is controlled within the above range to ensure alloy formation in the catalyst without wasting raw materials.
[0030] The amount of ethylene glycol added is preferably 10 to 30 mL, more preferably 20 mL. There is no particular limitation on the operation of dissolving the platinum salt and the transition metal salt in ethylene glycol, and a mixing technical solution well known to those skilled in the art can be used.
[0031] (2) adding the original biomass and its derivatives and the nitrogen precursor to the mixture obtained in step (1), stirring and solvent thermally treating;
[0032] Wherein, the biomass derivative includes cellulose and / or lignin and / or glucose, preferably lignin. The nitrogen precursor includes glutamic acid and / or glycine and / or urea and / or ammonium sulfate, preferably urea. The present invention has no special limitation on the source of the native biomass, and various straws well known to those skilled in the art can be used. The present invention has no special limitation on the source of the biomass derivative and the nitrogen precursor, and commercially available products well known to those skilled in the art can be used.
[0033] Among them, the mass ratio of the native biomass and its derivatives to the mass ratio of the platinum salt is preferably (2-5):1, more preferably 2:1; the molar ratio of the nitrogen precursor to the platinum salt is preferably (1-5):1, more preferably 3:1.
[0034] Among them, the present invention mixes the solid and the solution evenly by stirring, thereby promoting the coordination of the nitrogen precursor and the metal to form a bimetallic alloy active site during the solvothermal process, thereby obtaining a nitrogen-modified metal composite material with high catalytic efficiency. The stirring method is preferably magnetic stirring, the rotation speed is preferably 300 to 1000 rpm, more preferably 900 rpm; the stirring time is preferably 0.5 to 2 hours, more preferably 1 to 2 hours, and most preferably 1 hour; the present invention has no special requirements for the equipment of magnetic stirring, and a magnetic stirrer familiar to those skilled in the art can be used.
[0035] Among them, the temperature of the solvent thermal treatment is preferably 150-250°C, more preferably 180-220°C, and most preferably 195°C; the time of the solvent thermal treatment is preferably 6-18h, more preferably 10-18h, and most preferably 12h. If the solvent thermal temperature is too low, the original biomass and its derivatives are difficult to carbonize, which affects the formation of the alloy. If the temperature is too high, energy is wasted. To avoid the above problems, the temperature of the solvent thermal treatment is controlled within the above range in the present invention. During the solvent thermal treatment process, while the biomass is carbonized, the bimetal is reduced and loaded on the nitrogen-modified biochar carrier in the form of an alloy.
[0036] (3) After the solvent thermal treatment is completed, the product after the solvent thermal treatment is centrifuged, washed and dried in sequence to obtain a nitrogen-modified metal composite material.
[0037] The present invention has no special limitation on the centrifugation, washing and drying operations, and the centrifugation, washing and drying technical solutions well known to those skilled in the art can be used.
[0038] The centrifugal speed was 10000 rpm and the centrifugal time was 5 min.
[0039] Wherein, the detergent is anhydrous ethanol and water. The source of anhydrous ethanol is not particularly limited, and commercial products known to those skilled in the art can be used; water is preferably deionized water. The amount of detergent used is preferably 5 to 40 mL, and more preferably 10 to 30 mL. The number of times of washing with anhydrous ethanol is preferably 2 to 3 times; the number of times of washing with water is preferably 2 to 3 times. The washing process is preferably: the solid product after solvent thermal treatment is mixed with the detergent and then stirred and centrifuged in sequence. The stirring time is preferably 10 to 30 min; the stirring rate is preferably 200 to 300 rpm; the stirring method is preferably magnetic stirring.
[0040] The drying temperature is preferably 55 to 80°C, more preferably 60 to 65°C; the drying time is preferably 10 to 24 hours, more preferably 12 to 15 hours. In the present invention, the drying is preferably vacuum drying. The present invention has no special requirements for the drying equipment, and a vacuum drying oven commonly used in the art can be used.
[0041] In the embodiments of the present invention, the present invention uses various native biomass straws or biomass derivatives such as lignin as carbon sources to achieve resource utilization of agricultural waste; by carbonizing native biomass and its derivatives in ethylene glycol under the condition of adding various nitrogen precursors, and at the same time, the bimetallic is reduced and loaded on the nitrogen-modified functional carbon carrier to form alloy catalytic sites; the alloy catalytic sites contained are conducive to the adsorption of monosaccharides, promote mass transfer, and promote the oxidation of monosaccharides to the final product sugar acid, thereby achieving efficient monosaccharide oxidation reaction.
[0042] One embodiment of the present invention provides a nitrogen-modified metal composite material prepared according to the above preparation method, wherein the nitrogen-modified functional carbon carrier is a nitrogen-modified biochar carrier, and the nitrogen-modified biochar carrier contains pyridinic nitrogen and pyrrolic nitrogen (these two forms of nitrogen do not exist as independent entities, but as different chemical states of nitrogen element in the carbon carrier); the bimetallic alloy includes Pt3Zn alloy and PtZn 1.7 And other alloy structures.
[0043] An embodiment of the present invention provides an application of a nitrogen-modified metal composite material in catalyzing the preparation of sugar acid from monosaccharides. The specific application is: the nitrogen-modified metal composite material is mixed with monosaccharides, ultrapure water, and oxygen, and then an oxidation reaction is carried out to obtain sugar acid; the monosaccharides include xylose and glucose, and xylose is converted into xylonic acid through an oxidation reaction, and glucose is converted into gluconic acid and glucaric acid through an oxidation reaction.
[0044] The nitrogen-modified metal composite material, monosaccharide and ultrapure water are mixed in a magnetic stirring high-pressure reactor. There is no special limitation on the model of the instrument, and a common magnetic stirring high-pressure reactor in the art can be used. Pure oxygen is introduced into the magnetic stirring high-pressure reactor for 3 to 4 times, and the oxygen pressure is preferably 0.1 to 1.4 MPa, more preferably 0.6 to 1 MPa, and most preferably 1 MPa.
[0045] The mass concentration of monosaccharide in the mixed solution is preferably 1-10%, more preferably 10%; the mass ratio of nitrogen-modified metal composite material to monosaccharide is preferably 1:(2-10), more preferably 1:(2-5).
[0046] Wherein, the temperature of the oxidation reaction is preferably 60-110°C, more preferably 80-100°C, and the time is preferably 10-120 min, more preferably 30-60 min; or the temperature is preferably 25-50°C, and the time is preferably 1-5 d, more preferably 1-3 d. The present invention preferably controls the temperature and time of the oxidation reaction within the above range, which is conducive to promoting the complete conversion of monosaccharides. In the present invention, the rate of the oxidation reaction is preferably 500-800 rpm.
[0047] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0048] Example 1: 0.2 g of chloroplatinic acid and 0.4 g of zinc chloride were dissolved in 20 mL of ethylene glycol (the molar ratio of chloroplatinic acid to zinc chloride was 1:6), transferred to 100 mL of polytetrafluoroethylene, 0.4 g of crushed rice straw and 0.04 g of urea (the mass ratio of rice straw to chloroplatinic acid was 2:1, and the molar ratio of urea to chloroplatinic acid was 2.8:1), and heated at 195 ° C for 12 h in a high temperature and high pressure reactor. After the solvent thermal treatment, a solid material was obtained by centrifugation at 10000 rpm for 5 min, washed 3 times with anhydrous ethanol, washed 2 times with ultrapure water, and finally vacuum dried at 60 ° C for 12 h to obtain a nitrogen-modified metal composite material (PtZn / U).
[0049] Figure 1 This is a transmission electron microscope image of the nitrogen-modified metal composite material prepared in Example 1. Figure 1 It can be seen that the material is spherical and the average particle size is about 3.37nm.
[0050] Figure 2 This is the XPS spectrum of the Pt 4f orbital of the nitrogen-modified metal composite material prepared in Example 1. After peak fitting of the XPS spectrum, it was found that the 4f orbital of Pt 5 / 2 and 4f 7 / 2 The peak difference of the state is 3.3 eV, indicating that the Pt on the surface of the material is Pt 0 exists in the form of.
[0051] Figure 3 This is the infrared spectrum of the nitrogen-modified metal composite material prepared in Example 1. Figure 3 It can be seen that the surface of the material is rich in oxygen-containing functional groups such as COOH, OH and Zn-N bonds.
[0052] Example 2: Take 0.2g of chloroplatinic acid and 0.4g of zinc chloride and dissolve them in 20mL of ethylene glycol (the molar ratio of chloroplatinic acid to zinc chloride is 1:6), transfer them to 100mL of polytetrafluoroethylene, add 0.4g of crushed rice straw and 0.1g of glycine (the mass ratio of rice straw to chloroplatinic acid is 2:1, and the molar ratio of glycine to chloroplatinic acid is 2.8:1), and heat them at 195°C for 12h in a high-temperature and high-pressure reactor. After the solvent thermal treatment, the solid material was obtained by centrifugation at 10000rpm for 5min, washed 3 times with anhydrous ethanol, washed 2 times with ultrapure water, and finally vacuum dried at 60°C for 12h to obtain a nitrogen-modified metal composite material (PtZn / G).
[0053] Example 3: Take 0.2g of chloroplatinic acid and 0.4g of zinc chloride and dissolve them in 20mL of ethylene glycol (the molar ratio of chloroplatinic acid to zinc chloride is 1:6), transfer them to 100mL of polytetrafluoroethylene, add 0.4g of lignin and 0.04g of urea (the mass ratio of lignin to chloroplatinic acid is 2:1, and the molar ratio of urea to chloroplatinic acid is 2.8:1), and heat them at 195°C for 12h in a high-temperature and high-pressure reactor. After the solvent thermal treatment, the solid material was obtained by centrifugation at 10000rpm for 5min, washed 3 times with anhydrous ethanol, washed 2 times with ultrapure water, and finally dried in vacuum at 60°C for 12h to obtain a nitrogen-modified metal composite material (PtZn / UL).
[0054] Application Example 1: Take 0.02 g of the nitrogen-modified metal composite material (PtZn / U) prepared in Example 1, 0.05 g of glucose, and 5 mL of ultrapure water and mix them evenly to obtain a mixed solution (the mass concentration of glucose in the mixed solution is 10%, and the mass ratio of the nitrogen-modified metal composite material to glucose is 1:2.5). Then transfer the mixed solution to a high-pressure reactor, fill it with 1 MPa of oxygen, and carry out oxidation reaction at 100°C accompanied by magnetic stirring at a rate of 800 rpm; after 1 h, the reaction is completed, and the reaction mixture is quickly cooled in an ice-water bath, and then filtered using a 0.2 μm filter membrane (polyethersulfone membrane), and the filtered solution is used to determine the product by HPLC, and the yield of gluconic acid is calculated.
[0055] The HPLC conditions are as follows: the chromatographic column is Aminex HPX-87H, the mobile phase is 0.6 mL / min sulfuric acid solution (5 mM), the column temperature is 50°C, and the injection volume is 20 μL. The gluconic acid detector is an ultraviolet detector that measures the sample components at 210 nm, and the detector temperature is 25°C. The glucose detector is a differential detector, and the detector temperature is 35°C.
[0056] The final yield of gluconic acid was 81.7%, the yield of glucaric acid was 13.1%, and the conversion rate of glucose was 100%.
[0057] Application Example 2: Take 0.02 g of the nitrogen-modified metal composite material (PtZn / G) prepared in Example 2, 0.05 g of glucose, and 5 mL of ultrapure water and mix them evenly to obtain a mixed solution (the mass concentration of glucose in the mixed solution is 10%, and the mass ratio of the nitrogen-modified metal composite material to glucose is 1:2.5). Then transfer the mixed solution to a high-pressure reactor, fill it with 1 MPa of oxygen, and carry out oxidation reaction at 50°C accompanied by magnetic stirring at a rate of 800 rpm. After 2 days, the reaction is completed, and the reaction mixture is quickly cooled in an ice-water bath, and then filtered with a 0.2 μm filter membrane (polyethersulfone membrane). The filtered solution is used to determine the product by HPLC, and the yield of gluconic acid is calculated.
[0058] The conditions of HPLC are the same as those of HPLC in Application Example 1.
[0059] The final yield of gluconic acid was 78.7%, the yield of glucaric acid was 17.6%, and the conversion rate of glucose was 100%.
[0060] Application Example 3: Take 0.01 g of the nitrogen-modified metal composite material (PtZn / UL) prepared in Example 3, 0.05 g of glucose, and 5 mL of ultrapure water and mix them evenly to obtain a mixed solution (the mass concentration of glucose in the mixed solution is 10%, and the mass ratio of the nitrogen-modified metal composite material to glucose is 1:5), and then transfer the mixed solution to a high-pressure reactor, and carry out an oxidation reaction in the air exposed to 25°C, accompanied by magnetic stirring at a rate of 800 rpm; after 2 days, the reaction is completed, and the reaction mixture is quickly cooled in an ice-water bath, and then filtered using a 0.2 μm filter membrane (polyethersulfone membrane), and the filtered solution is used to determine the product by HPLC, and the yield of gluconic acid is calculated.
[0061] The conditions of HPLC are the same as those of HPLC in Application Example 1.
[0062] The final yield of gluconic acid was 79.2%, the yield of glucaric acid was 7.3%, and the conversion rate of glucose was 100%.
[0063] Figure 4 The yield of gluconic acid produced by catalytic conversion of glucose by the nitrogen-modified metal composite material prepared in Example 3 under different reaction temperature conditions varies with reaction time. Figure 4 It can be seen that the nitrogen-modified metal composite material prepared in Example 3 of the present invention can be used as a catalyst to catalyze the oxidation reaction of monosaccharides, and at 60-100° C., glucose can be efficiently catalyzed into sugar acid, wherein the maximum yield of gluconic acid is 86.8%.
[0064] The calculation formula for the yield of each sugar acid is:
[0065] Gluconic acid yield (%) = gluconic acid production (mol) / glucose sugar unit (mol) × 100%;
[0066] Glucaric acid yield (%) = glucaric acid production (mol) / glucose unit (mol) × 100%;
[0067] Xylonic acid yield (%) = xylonic acid production (mol) / xylose sugar unit (mol) × 100%.
[0068] The above is only a preferred embodiment of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.
Claims
1. A method for preparing a nitrogen-modified metal composite material, characterized in that: The following steps are involved: Step 1, dissolving a platinum salt and a transition metal salt in ethylene glycol to obtain a mixture; the platinum salt comprises chloroplatinic acid and / or platinum diacetylacetonate, and the transition metal salt comprises zinc chloride and / or nickel nitrate and / or cupric chloride; Step 2: adding the native biomass and its derivatives and the nitrogen precursor to the mixture obtained in step 1, stirring and solvent thermal treatment, centrifuging, washing and drying the product after solvent thermal treatment in sequence to obtain a nitrogen-modified metal composite material; the native biomass and its derivatives include rice straw and / or lignin and / or glucose, and the nitrogen precursor includes glutamic acid and / or glycine and / or urea and / or ammonium sulfate.
2. The preparation method according to claim 1, characterized in that: In step 1, the molar ratio of the platinum salt to the transition metal salt is (0.5-1):(1-10).
3. The preparation method according to claim 1, characterized in that: The amount of ethylene glycol added in step 1 is 10 to 30 mL.
4. The preparation method according to claim 1, characterized in that: In step 2, the mass ratio of the primary biomass and its derivatives to the platinum salt is (2-5):
1.
5. The preparation method according to claim 1, characterized in that: In step 2, the molar ratio of the nitrogen precursor to the platinum salt is (1-5):
1.
6. The preparation method according to claim 1, characterized in that: In the step 2, the stirring speed is 300-1000 rpm, and the stirring time is 0.5-2 hours; the temperature of the solvent thermal treatment is 150-250° C., and the solvent thermal treatment time is 6-18 hours.
7. A nitrogen-modified metal composite material obtained by the preparation method according to any one of claims 1 to 6, characterized in that: The metal is a bimetallic alloy nanoparticle, and the nitrogen-modified functional carbon carrier obtained by carbonizing native biomass and its derivatives in ethylene glycol containing a nitrogen precursor is a nitrogen-modified biochar carrier.
8. Use of the nitrogen-modified metal composite material according to claim 7 in catalyzing the preparation of sugar acid from monosaccharides, characterized in that: The specific application is: the nitrogen-modified metal composite material is used as a catalyst, mixed with monosaccharide, ultrapure water and oxygen, and then subjected to oxidation reaction to obtain sugar acid; after the reaction is completed, the reaction kettle is cooled with running water and the pressure in the reaction kettle is released, and the supernatant is taken for qualitative and quantitative analysis of the product by high performance liquid chromatography; The monosaccharides include xylose and glucose. Xylose is converted into xylonic acid through oxidation reaction, and glucose is converted into gluconic acid and glucaric acid through oxidation reaction.
9. The use according to claim 8, characterized in that: The temperature of the oxidation reaction is 60-110°C or 25-50°C; when the reaction temperature is 60-110°C, the reaction time is 10-120 minutes; when the reaction temperature is 25-50°C, the reaction time is 1-5 days.
10. The use according to claim 8, characterized in that: The mass concentration of monosaccharide in the mixed solution of nitrogen-modified metal composite material, monosaccharide, ultrapure water and oxygen is 1-10%; the mass ratio of the nitrogen-modified metal composite material to monosaccharide is 1:(2-10); and the oxygen pressure is 0.1-1.4MPa.
Citation Information
Cited By
Platinum-zinc loaded carbon nanotube catalyst as well as preparation method and application thereof
CN121060522A